2009
DOI: 10.1101/gad.1798209
|View full text |Cite
|
Sign up to set email alerts
|

Three subclasses of a Drosophila insulator show distinct and cell type-specific genomic distributions

Abstract: Insulators are protein-bound DNA elements that are thought to play a role in chromatin organization and the regulation of gene expression by mediating intra-and interchromosomal interactions. Suppressor of Hair-wing [Su(Hw)] and Drosophila CTCF (dCTCF) insulators are found at distinct loci throughout the Drosophila melanogaster genome and function by recruiting an additional protein, Centrosomal Protein 190 (CP190). We performed chromatin immunoprecipitation (ChIP) and microarray analysis (ChIP-chip) experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
312
3
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(345 citation statements)
references
References 52 publications
28
312
3
2
Order By: Relevance
“…Previous studies have shown that Drosophila insulator proteins are present at hundreds of sites throughout the genome that colocalize to distinct foci predominantly around the nuclear periphery in diploid cells (Ramos et al 2006;Gerasimova et al 2007). A number of proteins have been identified that interact with insulator DNA but additional components may be required to explain all the properties of these sequences (Pai et al 2004;Capelson and Corces 2005;Lei and Corces 2006;Bushey et al 2009). The research project carried out by students in the RISE program seeks to find novel protein components of insulator complexes as well as other proteins that may have unique roles in nuclear organization.…”
Section: Choice Of a Research Topic For The Rise Programmentioning
confidence: 99%
“…Previous studies have shown that Drosophila insulator proteins are present at hundreds of sites throughout the genome that colocalize to distinct foci predominantly around the nuclear periphery in diploid cells (Ramos et al 2006;Gerasimova et al 2007). A number of proteins have been identified that interact with insulator DNA but additional components may be required to explain all the properties of these sequences (Pai et al 2004;Capelson and Corces 2005;Lei and Corces 2006;Bushey et al 2009). The research project carried out by students in the RISE program seeks to find novel protein components of insulator complexes as well as other proteins that may have unique roles in nuclear organization.…”
Section: Choice Of a Research Topic For The Rise Programmentioning
confidence: 99%
“…28 This protein is essential for enhancer blocking of the Su (Hw) insulator and also interacts with other Drosophila insulator proteins, dCTCF 29,30 and BEAF. 31 Although the BTB domain of CP190 does not belong to the ttk group, it is suggested to play a significant role in supporting long-distance interactions between insulators.…”
Section: Introductionmentioning
confidence: 99%
“…Although insulators would be expected to reside primarily in intergenic regions where they could provide boundary or enhancer blocking activity, genome scans of CTCF enrichment show that CTCF sites are overrepresented in genes and promoter regions, with only 41-56% at intergenic locations (5). In Drosophila, between about 49% and 64% of insulator sites are located in intergenic regions (4). Thus, although CTCF sites are proposed to be insulators, their in vivo functions may not be limited to insulation.…”
mentioning
confidence: 99%
“…Evidence also suggests that insulators are involved in higher-order chromatin organization by clustering together with other insulators. Such "insulator bodies" can be visualized at the nuclear periphery of certain cells in Drosophila and are thought to coalesce through the interaction of proteins such as Su(Hw) and Drosophila CTCF (3,4).…”
mentioning
confidence: 99%